2012
DOI: 10.1002/jor.22168
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff tear reduces muscle fiber specific force production and induces macrophage accumulation and autophagy

Abstract: Summary Full-thickness tears to the rotator cuff can cause severe pain and disability. Untreated tears progress in size and are associated with muscle atrophy and an infiltration of fat to the area, a condition known as “fatty degeneration.” To improve the treatment of rotator cuff tears, a greater understanding of the changes in the contractile properties of muscle fibers and the molecular regulation of fatty degeneration is essential. Using a rat model of rotator cuff injury, we measured the force generating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
159
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(176 citation statements)
references
References 64 publications
13
159
4
Order By: Relevance
“…Mendias et al corroborated these findings, and further showed diminished force production in muscle fibers isolated from chronic, full-thickness tears 16 . Animal models of rotator cuff disease, particularly large animal models, are relatively effective in recapitulating this atrophic, fat-accumulating phenotype of early and midstage disease [29][30][31][32][33][34][35] . However, to our knowledge, no previous study involving humans or animals has addressed the existence of degeneration or the tissue-level pattern of fat accumulation within the muscle in the most chronic and advanced stage of rotator cuff disease.…”
mentioning
confidence: 99%
“…Mendias et al corroborated these findings, and further showed diminished force production in muscle fibers isolated from chronic, full-thickness tears 16 . Animal models of rotator cuff disease, particularly large animal models, are relatively effective in recapitulating this atrophic, fat-accumulating phenotype of early and midstage disease [29][30][31][32][33][34][35] . However, to our knowledge, no previous study involving humans or animals has addressed the existence of degeneration or the tissue-level pattern of fat accumulation within the muscle in the most chronic and advanced stage of rotator cuff disease.…”
mentioning
confidence: 99%
“…Examples include studies that have evaluated the effects of aging 12 , exercise 10,13,14 , spaceflight 15 , injury 2,3,16 , drug treatments 17,18 , disease 19 and genetic manipulation 20,21 on fiber structure and function. Due to the ability to directly assess the contractile performance of myofibrils in their native configuration, this technique provides an attractive platform from which to form an understanding of myofibrillar function absent of potentially confounding effects that are present when neuromuscular signal transmission and excitation-induced calcium release are included in the system under study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, alternative means for exposing the fiber to the various experimental solutions could be employed, including devising a manually-operated system of chambers or a single chamber that allows for rapid filling and emptying of solutions. Finally, while sub-physiological experimental temperatures such as 15 °C are commonly used to improve the reproducibility of mechanical measurements 1,2,3,5,8,12,17,27 . Other approaches to solution composition have been employed with notable success by other research groups and typically make use of published binding constants and computational tools 27,30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether the plasma membrane of muscle fibers from chronically torn rotator cuff muscles is damaged during repair, we used a well-established rat model of full-thickness rotator cuff tears [12,18,24]. Evans Blue Dye (EBD) is a water-soluble, membrane-impermeable dye that accumulates in the cytosol of muscle fibers that have sustained an injury to their plasma membrane [14].…”
Section: Introductionmentioning
confidence: 99%